2020
DOI: 10.1159/000511196
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and Impaired Renal Function: A Prospective Cohort Study

Abstract: <b><i>Background:</i></b> Related studies have demonstrated a relationship of elevated serum uric levels with a decline in kidney function. However, limited evidence exists in a Southeast Asian community-based population. <b><i>Objective:</i></b> The study aimed to examine the relationship between serum uric acid levels and impaired renal function. <b><i>Methods:</i></b> A prospective cohort study was conducted in the Thai army health chec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…In our two previous clinical trials, the oral administration of the combined dose of glycine and tryptophan led to a decreased concentration of serum uric acid because of the increased urate excretion into the urine [20,21]. A recent prospective cohort study suggested that serum uric acid levels are independently associated with the incidence of impaired renal function and renal progression [22], and a meta-analysis reported that uric acid-lowering therapy effectively regards CKD progression [23]. Furthermore, serum uric acid is associated with CKD incidence [24,25].…”
Section: Introductionmentioning
confidence: 93%
“…In our two previous clinical trials, the oral administration of the combined dose of glycine and tryptophan led to a decreased concentration of serum uric acid because of the increased urate excretion into the urine [20,21]. A recent prospective cohort study suggested that serum uric acid levels are independently associated with the incidence of impaired renal function and renal progression [22], and a meta-analysis reported that uric acid-lowering therapy effectively regards CKD progression [23]. Furthermore, serum uric acid is associated with CKD incidence [24,25].…”
Section: Introductionmentioning
confidence: 93%
“…Hyperuricemia (HUA) is a status of high SUA concentration, which may lead to urate crystals being deposited in joints, tendons, and other tissues, and could also elevate the risk of gout or other comorbidities development [ 4 , 5 ]. Besides gout, the relationships between HUA and dyslipidemia [ 6 ], cardiovascular disease (CVD) [ 7 ], metabolic syndrome (MetS) [ 4 ], insulin resistance [ 8 ], hypertension [ 9 ] or renal disease [ 10 ] have been observed in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…A separate significant finding worth noting was that the association between hyperuricemia and the new onset of CKD in males was relatively stronger than that in females, with the adjusted HR of hyperuricemia for CKD being 1.925 (1.724–2.150) and 1.676 (1.530–1.848) for males and females, respectively. Previous studies have investigated sex differences in the correlations between hyperuricemia and incident CKD but obtained mixed results [ 13 , 42 , 43 ]. Estrogen is the most commonly considered reason for this sex difference, as it can cause the excretion of urate through urine [ 44 ] and inhibit the generation of uric acid by xanthine oxidase [ 45 ].…”
Section: Discussionmentioning
confidence: 99%